MAGNETIC NANOPARTICLE HYPERTHERMIA IN CANCER TREATMENT - Giustini, Andrew J. (2010)
The activation of magnetic nanoparticles (mNPs) by an alternating magnetic field (AMF) is currently being explored as technique for targeted therapeutic heating of tumors. Various types of superparamagnetic and ferromagnetic particles, with different coatings and targeting agents, allow for tumor site and type specificity. Magnetic nanoparticle hyperthermia is also being studied as an adjuvant to conventional chemotherapy and radiation therapy. This review provides an introduction to some of the relevant biology and materials science involved in the technical development and current and future use of mNP hyperthermia as clinical cancer therapy.